Redescription of Culex (Culex) brethesi Dyar, 1919 (Diptera: Culicidae) - C., Rossi Gustavo (Zootaxa, 2006)
Culex (Culex) brethesi Dyar is redescribed in the adult, pupal and fourth-instars larvae and the male genitalia. The paper includes available information on the taxonomy and distribution of the species. The taxonomy and identification of Cx. brethesi are reviewed in light of current knowledge of the subgenus Culex.